Budaya Game Mobile Legends: Kajian pada Bang Bang Kelompok Gamers Vol’Jin di Jepara - Anggraeni Tysa Soesanto; Budi Puspo Priyadi; Risis Tiani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
In the digital era that has developed increasingly modern, online games have begun to become part of the lifestyle of some Indonesians, especially after the development of Android-based smartphones. This is due to an increase in the number of game players from various game genres that have emerged. Each individual has various ways to meet their entertainment needs, which are not limited by space, time or age, such as playing online games. Multiplayer Online Battle Arena (MOBA) is a video game genre using strategy. Mobile Legends: Bang Bang is a game with the MOBA genre developed and released by Moonton. Mobile Legends: Bang Bang uses a game system or gameplay that is easier for beginner gamers to understand and also the appearance used is more attractive so that it is in great demand by various groups. Researchers use the topic of discussion with the theory of symbolic interactionism as anything related to the formation of meaning. The focus of this research is to discuss how the system or meaning value in the VOL'JIN Gamers Group. In this case, the researcher focuses on how this meaning system has an impact on the existence of the online game Mobile Legends: Bang Bang (MLBB) because in the meaning system it will be seen how social, cultural, and human behavior phenomena in today's modern era. Especially on the behavior patterns of playing these online games. The factors that cause gaming behavior in the VOL'JIN Gamers Group, namely curiosity, relieving stress, following trends, generating additional income and a high level of playing difficulty. Therefore, there is a process of pursuing the meaning of competition for prestige and expecting praise from others.